2009
DOI: 10.3844/ajas.2009.172.178
|View full text |Cite
|
Sign up to set email alerts
|

A Combining Ability Analysis of Cassava Manihot esculenta Crantz Genotypes to Anthracnose Disease

Abstract: Cassava Anthracnose Disease (CAD) caused by Colletotrichum gloeosporioides f sp. manihotis has been recognized as one of the major economic disease of cassava in all the cassava growing regions of Africa. Little information is available on the resistance of cassava to C. gloeosporioides f sp. manihotis. This study was conducted to determine the relative importance of general (GCA) and specific (SCA) combining ability, maternal and non-maternal reciprocal effects on resistance to C. gloeosporioides f sp. maniho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 4 publications
(5 reference statements)
2
8
0
Order By: Relevance
“…This observation is supported by the argument that the ratio of additive to non-additive variance in a population gives an indication of relative importance of GCA and SCA estimates in predicting progeny performance (Owolade et al, 2009).…”
Section: Genetic Variability and Inheritance Of Rdmsupporting
confidence: 63%
“…This observation is supported by the argument that the ratio of additive to non-additive variance in a population gives an indication of relative importance of GCA and SCA estimates in predicting progeny performance (Owolade et al, 2009).…”
Section: Genetic Variability and Inheritance Of Rdmsupporting
confidence: 63%
“…Therefore, Maunjili can be a desirable parent for hybrids as well as for inclusion in breeding program aimed at developing varieties resistant to CGM due to its significant negative value (Table 3). The foregoing suggestion is in tandem with the report by Owolade et al (2008) andDa Silva (2008). The study has found that the best rated general combiners based on GCA effects were Mulola for average root number, fresh root weight and above ground weight and Maunjili for fresh root weight, harvest index and cassava green mite which means that these could be good parents to use when breeding for genotypes for the said traits.…”
Section: Resultssupporting
confidence: 64%
“…For CGM, significant positive combining ability effects were considered as low, non-significant as average and significant negative as high (Saleem, 2008). GCA and SCA values with negative effects show contribution towards resistance, and positive values show contribution towards susceptibility for CGM (Owolade et al, 2008). Baker's prediction ratio (PR) (Baker, 1978) was used in determining progeny performance, that is, .…”
Section: Test Of Significance For Combining Ability Effectsmentioning
confidence: 99%
“…It is the third most important source of carbohydrates in Africa [2] and the second most important staple crop in Ghana [3]. Cassava serves as food for over 800 million people worldwide [4], providing about 500 calories daily for more than 70 million people [5].…”
Section: Introductionmentioning
confidence: 99%